Correlation between esophageal pH-metry and esophagitis in gastroesophageal reflux disease in children. Issue 37 (September 2018) - Lupu, Vasile Valeriu; Burlea, Marin; Nistor, Nicolai; Streanga, Violeta; Starcea, Magdalena Iuliana; Paduraru, Gabriela; Ghica, Dragos Catalin; Mitrofan, Elena Cristina; Moscalu, Mihaela; Ignat, Ancuta
Abstract : Abstract: Gastroesophageal reflux (GER) is the intermittent or permanent passage of stomach content into the esophagus and gastroesophageal reflux disease (GERD) is the reflux which triggers a whole set of symptoms or complications. The study compares the 24-hours esophageal pH-metry, used for diagnosis of the GERD, with the esophagitis degree observed at the upper digestive endoscopy. 72 children were included, aged over 4 years old, admitted in a pediatric gastroenterology regional center in Northeast Romania, diagnosed with GERD by 24 hours pH-metry (with a positive Boix–Ochoa score), which also underwent the upper digestive endoscopy. Out of the 72 children diagnosed with GERD, 47 (65.28%) had grade A esophagitis and 25 (34.72%) grade B esophagitis. In GERD associated with grade B esophagitis the Boix–Ochoa score is statistically significant higher, compared with the GERD associated with grade A esophagitis ( F = 9.76, P = .0036, 95% CI). Upper digestive endoscopy performed in patients with gastroesophageal reflux disease shows the constant presence of esophagitis at all patients. There were only grade A and B esophagitis due to the fact that they are young patients with a relative short history of the disease. The correlation tests show a perfect parallel between the pH-metry scores and the endoscopic lesion. The correlation is so accurate that the pH-metry scores can be sufficient to prove GERD and the grade of esophagitis, the upper digestive endoscopy being reserved only for the cases that does not respond to the medical treatment or have other complications.